The Sociology of Chinese Capitalism in Southeast Asia Challenges and Prospects - Santasombat, Yos (Springer Nature Singapore : Imprint: Palgrave Macmillan, 2019)
Set within the context of ASEAN integration, this book considers how Capitalism from China interacts with the ASEAN Economic Community, considering the issue from a variety of sociological, cultural and economic perspectives. It examines some of the creative strategies - de-sinicization, re-sinicization and re-balancing - employed by local Chinese communities and ASEAN countries to cope with the pressures of Chinese capitalism. The book addresses the phenomenon of Chinese ethnic economic migration, particularly the social capital of being Chinese in South East Asia, as well as community building, the interplay between domestic politics and globalization, and the rise of Chinese tourism related entrepreneurship.